Improving therapeutic efficacy of IL-12 intratumoral gene electrotransfer through novel plasmid design and modified parameters. Issue 2 (April 2018) - Burkart, C.; Mukhopadhyay, A.; Shirley, S.; Connolly, R.; Wright, J.; Bahrami, A.; Campbell, J.; Pierce, R.; Canton, D.
Abstract The use of immunomodulatory cytokines has been shown effective in regressing a wide range of tumors. However, systemic delivery of recombinant cytokines results in serious, potentially life-threatening, adverse effects. By contrast, nucleic acid transfer via electroporation (EP) is a safe and effective method of delivering plasmid-encoded cytokines to tumors. Intratumoral delivery of IL-12 plasmid DNA by electroporation (IT-pIL12-EP) produced objective response rates in Phase 2 clinical trials in metastatic melanoma. However, only 17.9% of patients receiving IT-pIL12-EP show a complete therapeutic response. Here, we sought to improve the antitumor efficacy of our clinical IT-pIL12-EP plasmid electroporation platform. We evaluated multiple plasmid designs for IL-12 expression. IL-12 expression from a plasmid incorporating a picornavirus-derived co-translational P2A site was the most effective in expressing IL-12p70. In addition, modifying the electroporation parameters improved transfection efficiency and expression of plasmid-derived IL-12p70, as well as its downstream effector IFN-γ in vivo. Finally, using a murine melanoma model that is representative of the intended target patient population, we show that combining modified electroporation conditions with the pIL12-P2A plasmid expression enhances the systemic antitumor response. These improvements to the IT-pIL12-EP platform may improve patient clinical response rates and survival when translated to clinical trials.